Diversification of Vibrio anguillarum Driven by the Bacteriophage CHOED - León, Marcela; Kokkari, Constantina; García, Katherine; Castillo, Daniel; Katharios, Pantelis; Bastías, Roberto (Frontiers in Microbiology, 2019)
Bacteriophages are an important factor in bacterial evolution. Some reports suggest that lytic bacteriophages can select for resistant mutant strains with reduced virulence. The present study explores the role of the bacteriophage CHOED in the diversification and virulence of its host Vibrio anguillarum. Nine phage-resistant strains were analyzed for their phenotype and different virulence factors, showing alterations in their fitness, motility, biofilm formation, lipopolysaccharide profiles and/or protease activity. Seven of the nine phage-resistant strains showed virulence reduction in a Sparus aurata larvae model. However, this is not generalized since two of the resistant strains show equal virulence than the parental strain. The genomic analysis of representative resistant strains, displayed that the majority of the mutations are specific for each isolate affecting genes related to lipopolysaccharide biosynthesis, quorum sensing, motility, toxin and membrane transport. The observed mutations were in agreement with the phenotypic and virulence differences observed. These results suggest that the phage CHOED acts as a selective pressure on V. anguillarum, allowing proliferation of resistant strains with different genotypes, phenotypes and degrees of virulence, contributing to bacterial diversification